Use of artificial intelligence in public sector: threats and prospects - Kaczmarek, Krzysztof; Karpiuk, Mirosław; Spaziani , Andrea (Studia Iuridica Toruniensia, 2025)
The aim of the article is to analyse the possibilities of using artificial intelligence in the public sector and to identify both the opportunities and threats posed by this digital tool. The authors showed that, thanks to advanced data analysis capabilities, automation of administrative processes, and crisis management, AI can significantly improve the efficiency and quality of public services. However, the implementation of this technology in the public sector is associated with several challenges, including system security, personal data protection, and transparency of decisionmaking processes. In the conclusions, the authors emphasise that the implementation of artificial intelligence in the public sector requires a balanced approach that takes into account both benefits and risks.